Disappearing alphabet (The) - Wilbur, Richard (San Diego : Voyager Books, 1998)
A collection of twenty-six short poems pondering what the world would be like if any of the letters of the alphabet should disappear.
Keywords: English language -- Alphabet -- Juvenile poetry; Children's poetry, American